Hospital Management Strategy in Improving Adaptive and Innovative Human Resources - Nugroho, Maulana Adjie; Purwadhi, Purwadhi; Kusnadi, Dadang (CV. Civiliza Publishing, 2025)
This study aims to explore hospital HRM strategies through a narrative review approach with thematic analysis of academic literature and policy documents published between 2016 and 2025. The review reveals that effective HRM strategies include the implementation of transformational leadership, an organizational culture that supports continuous learning, digitalization of HR processes, and incentive systems that foster innovation. Key instruments in enhancing healthcare workers’ adaptive capacity include reskilling and multiskilling programs, online learning platforms, and Human Resource Information Systems (HRIS). However, challenges such as resistance to change, limited resources, structural bureaucracy, and weak evaluation systems hinder effective implementation. This study concludes that strengthening the integration of structural, cultural, and technological aspects is crucial to building hospital human resources that are resilient, responsive, and highly competitive. The practical implications provide strategic guidance for hospital management, policymakers, and educational institutions in designing more contextual and sustainable HR development programs.